Cost Optimization of Mortars Containing Different Pigments and Their Freeze-Thaw Resistance Properties - Yildizel, Sadik Alper; Ozturk, Ali Ugur; Kaplan, Gökhan (Hindawi Limited, 2016)
Nowadays, it is common to use colored concrete or mortar in prefabricated concrete and reinforced concrete construction elements. Within the scope of this study, colored mortars were obtained with the addition of brown, yellow, black, and red pigments into the white cement. Those mixtures are examined for their compressive strength, unit weight, water absorption, and freeze-thaw resistance. Subsequent to comparison of these properties, a cost optimization has been conducted in order to compare pigment costs. The outcomes showed that the pore structure in architectural mortar applications plays an important role in terms of durability. And cost optimization results show that light colored minerals can be used instead of white cements.
Keywords: TA401-492; Materials of engineering and construction. Mechanics of materials